COVID-19 pandemic from the perspective of foreign volunteers in Poland - Khabirova, Aygul; Lipska, Katarzyna; Bartosiewicz-Kosiba, Patrycja; Kijanka, Emilia (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The aim of the article is to present the impact of the SARS-CoV-2 pandemic and the restrictions introduced on the situation of foreign volunteers who carried out their projects in Poland. The research was conducted between May and June 2020 by means of an individual, semi-structured interview with 20 volunteers of the European Solidarity Corps Programme. The analysis of the results indicated that the volunteers treated the outbreak of the pandemic as another challenge that they had to deal with. They focused on new responsibilities and personal development. They felt safe, were not afraid for their own health, had a stable financial situation and the support of people from the organizations they worked with, other volunteers, family and friends from their country of origin. It was important that they had a choice both in terms of taking on new responsibilities as well as when and how to continue the project.